Skills matter : additional results from the survey of adult skills - Organisation for Economic Co-operation and Development (OECD skills studies, ISSN 2307-8723, 2019)
Summary.
Keywords: osaaminen : arviointi : OECD-maat; oppiminen : arviointi : OECD-maat; koulutus : arviointi : OECD-maat; aikuiskoulutus; ammattitaito; lukutaito; tieto- ja viestintätekniikka